2018
DOI: 10.1016/j.joca.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin alters the cytokine and matrix-degrading enzyme profile during osteogenic and adipogenic MSC differentiation

Abstract: Visfatin-mediated increase of matrix mineralization and reduced collagen type I expression could contribute to bone fragility. Visfatin is involved in impaired bone remodeling at the adipose tissue/bone interface through induction of proinflammatory factors and dysregulated MMP/TIMP balance during MSC differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Leptin enhanced bone growth and maturation by increasing osteoblast number and activity through the peripheral pathways (Turner et al, 2013). Visfatin impaired bone remodeling via both inducing the pro‐inflammatory factors and dysregulating the MMP/TIMP balance during MSCs differentiation (Tsiklauri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Leptin enhanced bone growth and maturation by increasing osteoblast number and activity through the peripheral pathways (Turner et al, 2013). Visfatin impaired bone remodeling via both inducing the pro‐inflammatory factors and dysregulating the MMP/TIMP balance during MSCs differentiation (Tsiklauri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al found that MSC lineage fate determination is affected by cell energy metabolism and revealed a possible mechanism for senile osteoporosis, indicating that visfatin may affect MSC differentiation into adipocytes or osteoblasts [ 30 ]. Furthermore, Lali et al found that IL-8 levels are significantly increased by visfatin during MSC differentiation, and these elevated levels induce the differentiation of human bone marrow cells into osteoclasts [ 31 ]. Apart from the effects on osteoblast proliferation and collagen synthesis, visfatin also plays a crucial role in osteoclast formation by inhibiting osteoclastogenesis, which indicates its role in osteophyte formation in the context of inflammatory diseases [ 20 , 32 ].…”
Section: Roles Of Visfatin In Oamentioning
confidence: 99%
“…Exogenous administration of visfatin can stimulate human leukocytes to produce IL-1β, TNF-α, and IL-6 [37], or induce the secretion of IL-6, IL-8, and MCP-1 during osteogenic and adipogenic differentiation of MSCs [38]. Visfatin may also activate HUVEC to up-regulate the expression of VEGF and MMPs [39].…”
Section: Visfatin-primed Adscs Promote Tumor Stemness and Emt Throughmentioning
confidence: 99%